Beyond the Node Count: Metastatic Lymph Node Ratio as a Prognostic Marker in Locally Advanced Colorectal Cancer - Aytin, Yusuf Emre; Ozturk, Oguzhan Alp (The European Research Journal, 2026)
Objective: Colorectal cancer (CRC) remains a leading cause of cancer-related mortality, and staging based on the number of metastatic nodes may not fully reflect nodal tumor burden. The metastatic lymph node ratio (mLNR) has been proposed as a more informative prognostic marker, but its role in locally advanced CRC is unclear. This study aimed to evaluate the prognostic value of mLNR in patients with locally advanced (T3–T4), non-metastatic CRC and to identify an optimal cut-off for recurrence prediction.Methods: We retrospectively analysed 225 patients with T3–T4, non-metastatic CRC who underwent curative resection between 2015 and 2019. Disease-free survival (DFS) and overall survival (OS) were estimated using Kaplan–Meier analysis. Associations between mLNR, recurrence, stage and survival were examined with standard statistical tests. An optimal mLNR cut-off for recurrence was derived by receiver operating characteristic (ROC) analysis.Results: Patients with recurrence had significantly higher mLNR than recurrence-free patients. mLNR correlated inversely with DFS but not with OS. Higher mLNR was associated with T4 tumors and with higher AJCC stage. ROC analysis identified an mLNR cut-off of 0.1846 (area under the curve 0.643). Patients with mLNR ≥ 0.1846 had significantly shorter DFS and OS. A lymph node yield ≥12 was associated with longer DFS but not OS.Conclusion: mLNR is associated with recurrence, tumor stage and survival in locally advanced CRC, and a threshold around 0.18 may improve risk stratification beyond conventional node counts.